2013
DOI: 10.4049/jimmunol.1203533
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Histone Deacetylase Activity Suppresses IFN-γ Induction of Tripartite Motif 22 via CHIP-Mediated Proteasomal Degradation of IRF-1

Abstract: Tripartite motif (TRIM)22 plays an important role in IFN-mediated antiviral activity. We previously demonstrated that IFN regulatory factor (IRF)-1 was crucial for basal and IFN-induced TRIM22 transcription via binding to a novel cis-element named 5′ extended IFN-stimulating response element. In this study, we investigated the role of histone deacetylase (HDAC) activity in TRIM22 induction by IFN-γ and its underlying mechanism. We found that the HDAC activity, especially that conferred by HDAC6, was required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Western Blotting and Coimmunoprecipitation Assay-Western blotting assay and coimmunoprecipitation assay were performed as described previously (41,42 Statistical Analysis-Experimental data were presented as mean Ϯ S.E. of at least three independent experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Western Blotting and Coimmunoprecipitation Assay-Western blotting assay and coimmunoprecipitation assay were performed as described previously (41,42 Statistical Analysis-Experimental data were presented as mean Ϯ S.E. of at least three independent experiments.…”
Section: Methodsmentioning
confidence: 99%
“…A negative control was set up for each antibody by omitting the primary antibody (Supplementary Figure 6g) and specificity of primary antibodies was verified by immunoblotting throughout this research and also well confirmed by other groups as well. 37, 38, 39, 40, 41, 42, 43, 44, 45 The primary antibody incubation was completed at 4°C overnight in a humidified chamber with the following antibodies: mouse monoclonal antibody PI3K-p85 (sc-1673, Santa Cruz Biotechnology; dilution 1 : 150), 37, 38, 39, 40 mouse monoclonal antibody CHIP (sc-133066, Santa Cruz Biotechnology; dilution 1 : 200) 41, 42, 43 and mouse monoclonal antibody PCNA (Calbiochem; dilution 1 : 500). 44, 45 After incubation, each section was washed with PBS and incubated with the secondary biotinylated goat-anti mouse antibody (Vector Laboratories, Burlingame, CA, USA) for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…HATs are positive regulators of transcription in general. However, HDAC activity is also essential for transcriptional induction of ISGs [59][60][61][62][63][64]. HDAC activity has been reported to be required for recruiting RNA polymerase II to the promoters of ISGs [65], although how HDACs regulate the transcriptional activation of ISG remains unclear.…”
Section: Chromatin Modulatorsmentioning
confidence: 99%